The teff value chain on the move - Minten, Bart; Tamru, Seneshaw; Engida, Ermias; Kuma, Tadesse (International Food Policy Research Institute, 2013)
We study the value chain of teff, Ethiopia’s most important staple food crop by area and value. Based on large-scale primary surveys, we find significant changes in the last decade. First, there is increasing adoption of modern inputs (chemical fertilizer, improved varieties, and herbicides) by farmers, especially by those living close to urban centers. Second, quality demands are rising and there are important shifts from the cheap red varieties to the more expensive white ones. Third, we see an increasing willingness-to-pay for convenience in urban areas, as illustrated by the emergence of one-stop retail shops—that provide sales, cleaning, milling, and transport services—as well as by a sizable foodservice industry. Fourth, the share of rural–urban market-ing, urban distribution, and milling margins in final retail prices is declining, indicating improved marketing efficiency over time.